Efektivitas Fungsi Legislasi dan Pengawasan Dewan Perwakilan Rakyat Daerah dalam Penanganan Permasalahan Sampah Berdasarkan Perspektif Yuridis Normatif di Indonesia - Mellanie Destirani; Kms. Novyar Satriawan Fikri; Bambang Sasmita Adi Putra (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Indonesia’s commitment to the rule of law requires waste management policies to be implemented under clear and consistent legal frameworks. However, increasing waste problems have highlighted the need to strengthen the legislative and oversight functions of Regional People’s Representative Councils (DPRD). This study aims to examine the normative regulation of these functions, analyze the harmonization of relevant legislation, and formulate legal measures to improve their effectiveness in waste management. The research employs a normative juridical method using statutory and conceptual approaches based on library research, with qualitative prescriptive analysis. The findings reveal that Law Number 23 of 2014, Law Number 17 of 2014, Law Number 18 of 2008, and Law Number 13 of 2022 are generally harmonized in regulating governmental authority. Nevertheless, legal gaps remain, particularly the absence of specific oversight indicators for waste management and the lack of explicit DPRD authority in supervising waste policies. Strengthening regulatory provisions and institutional capacity is therefore necessary to enhance the effectiveness of the DPRD’s legislative and oversight functions in addressing waste management issues.